STRATEGI PEMASARAN BISNIS DALAM MENINGKATKAN PEMBELIAN PROMOSI DI MEDIA SOSIAL DAN KUALITAS PRODUK PADA YOWES MIE DI SITUBONDO - Sandra, Intan Ayu Kartika; Rachman, Riza; Mufid, Rozin Khairon; Febriyanto, Febriyanto; Khotip, Zainal; Ismayani, Meiriyanti (Fakultas Ekonomi dan Bisnis, 2022)
This research aims to gain an understanding of how important it is to increase purchases through promotions on social media and product quality at Yowes Mie Situbondo. Where promotion and product quality are very good at attracting consumer interest. And Yowes Mie also uses promotional media where he will get prizes on his Instagram. The ingredients used are very good, because Yowes Mie does not want to disappoint consumers. This article uses a qualitative method where the author interviews Yowes Mie by going directly to the field.